Od społecznika do profesjonalisty – ewolucja zawodu pracownika socjalnego w Polsce - Brenk, Mikołaj (Kultura-Społeczeństwo-Edukacja, 2012)
There are two main subjects raised in the article, meaning the development of the occupation of a social worker and the pursuit to make the work for the ones in need professional. The latter has its genesis in the actions taken in the period of annexation. Trials to nd an efficient method to help people in dealing with life crisis have not been fully achieved yet although lasting over a century. Therefore, there is a question whether and in what extend may the practice of the following decades be used to build the occupation of a social worker, which will gain a status of a profession.